Analisis Kepuasan Penumpang Gerbong Kereta Api Khusus Wanita menggunakan Model Servqual - Ispurwanto, Wing; Pricillia, Vany Widya (Humaniora, 2011)
To find women's representation of passenger satisfaction for the special woman carriage train service traveling the routes of Bogor to Jakarta, researcher performed a descriptive quantitative research with a population of rail passengers. Data taken from 80 respondents using incidental sampling technique is analyzed using the SERVQUAL model. Research results show that overall passenger satisfaction levels of service specific car is at the level of discontent. This can be seen from the gap between perceptions and negative expectations. Dimensions of service quality perceived by passengers are not satisfied that the dimensions of connection, reliability, response and physical evidence. However there are several dimensions of service quality perceived by passengers quite happy. Dimensions are empathy, facilities, security and comfort. This research concludes that there is a perception gap between the expectations of the ministry with a value of -1.101. Therefore, it is recommended to train the managers to improve service for passengers, especially the dimensions of felt unsatisfactory by passengers.